The Equal Parent Presumption: Social Justice in the Legal Determination of Parenting after Divorce - EDWARD KRUK (McGill-Queen's University Press, 2013)
The focus of this book is parenting after divorce and the best interests of children, in situations in which both parents are seeking to exclusively parent their children or are otherwise in conflict in regard to parenting after divorce. As such, the book will be of interest not only to divorce practitioners, policy-makers, academicians, and students, but also to parents themselves. After more than twenty-five years of studying the highly contentious issue of â€œchild custody,â€ my conclusion is that children of divorce will fare best if they are able to reside with each of their parents in an equal parenting arrangement, and that this key principle should be established as a presumption in law, and as fundamental to childrenâ€™s best interests and well-being. In the context of divorce, â€œequal parentingâ€ may be defined along three dimensions: 1 Equality of power and influence such that neither party is able to control the other or is in a submissive position to the other, so that the faculty of free consent may be fully exercised by each parent. Equality of opportunity to actively parent is a key element in this regard. 2 Equality of the proportion of residential time spent by each parent with the child after divorce relative to the amount of time each parent spent with the child prior to divorce. 3 Equality of residential time spent with the child after divorce relative to the other parent (50% time division). I will discuss how these three dimensions of gender equality are commensurate with a child-focused â€œbest-interests-of-thechild- from-the-perspective-of-the-childâ€ approach to the legal determination of child custody after divorce, and with a â€œresponsibility- to-needsâ€ approach to parenting after divorce. In addition, I argue that the state has a fiduciary obligation to enable arrangements for healthy parenting after divorce. In this regard, the standard of living in all households in which a child resides should be sufficient to allow the child to have his or her essential needs met, ideally through the active parenting of both parents. The ongoing, direct involvement of parents in childrenâ€™s lives is vitally important to their well-being; the need for roots (Weil 1943) and family connectedness are the most neglected needs among children in contemporary society, and especially so in an era of new genetic technologies and redefinitions of â€œparentâ€ in family law (Somerville 2006). Prevailing social policy in the Canadian child welfare field, including child protection and child care as well as child custody law and policy, serves largely to disconnect children from their families of origin (Neufeld and Mate 2004; Kruk 2011).